Deforestation and Forest Degradation: Drivers and Impacts on Biodiversity in Southeast Asia - Megan Koh; Ryan Teo; Ethan Tan (Journal of Selvicoltura Asean, 2024)
Deforestation and forest degradation in Southeast Asia pose significant threats to biodiversity and ecosystem services. Rapid economic development, agricultural expansion, and illegal logging are key drivers of these environmental changes. Understanding the underlying factors and their impacts is crucial for formulating effective conservation strategies. This research aims to identify the primary drivers of deforestation and forest degradation in Southeast Asia and to assess their impacts on biodiversity. The study seeks to provide insights that can inform policymakers and conservationists in addressing these pressing environmental issues. A mixed-methods approach was employed, combining quantitative data analysis from satellite imagery and forest cover assessments with qualitative interviews of local stakeholders. Case studies from Indonesia, Malaysia, and Thailand were analyzed to explore the relationships between human activities, forest loss, and biodiversity impacts. Findings reveal that agricultural expansion, particularly palm oil and timber production, is the leading cause of deforestation in the region. Biodiversity impacts include habitat loss, species extinction, and disruption of ecological processes. Local communities reported diminished resources and increased human-wildlife conflicts as direct consequences of forest degradation. The study concludes that urgent action is needed to mitigate deforestation and its ecological impacts in Southeast Asia. Effective policies must address the drivers of forest loss while promoting sustainable land-use practices. Collaborative efforts among governments, local communities, and conservation organizations are essential to safeguard biodiversity and enhance ecosystem resilience in the region.